2020
DOI: 10.1002/rth2.12418
|View full text |Cite
|
Sign up to set email alerts
|

Andexanet versus prothrombin complex concentrates: Differences in reversal of factor Xa inhibitors in in vitro thrombin generation

Abstract: Background Andexanet alfa (andexanet) is a modified human factor Xa (FXa) approved for anticoagulation reversal in patients with life‐threatening bleeding treated with rivaroxaban or apixaban. Four‐factor prothrombin complex concentrates (4F‐PCCs) are approved for reversal of vitamin K antagonist–induced anticoagulation but not FXa inhibitors. The mechanism and effectiveness of 4F‐PCCs for FXa inhibitor reversal are unclear. Objective To investigate the mechanism and impact of 4F‐PCCs on reversal of rivaroxaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…We observed in our in vitro experiments that andexanet alfa increased peak thrombin and velocity index to above normal, irrespective of the presence of FXaI. A similar increase in peak thrombin by andexanet alfa was observed by Lu and coworkers 19 . This increase in peak thrombin and velocity index may be caused by residual thrombin‐generating capacity of the FXa mutant or by neutralizing natural coagulation inhibitors including tissue factor pathway inhibitor (TFPI) 32 .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We observed in our in vitro experiments that andexanet alfa increased peak thrombin and velocity index to above normal, irrespective of the presence of FXaI. A similar increase in peak thrombin by andexanet alfa was observed by Lu and coworkers 19 . This increase in peak thrombin and velocity index may be caused by residual thrombin‐generating capacity of the FXa mutant or by neutralizing natural coagulation inhibitors including tissue factor pathway inhibitor (TFPI) 32 .…”
Section: Discussionsupporting
confidence: 81%
“…This 4F‐PCC is known to contain added heparin. Lu and coworkers treated their PCC with heparinase and reported that similar results were obtained with untreated‐ and heparinase‐treated plasma 19 . Lu and coworkers did not report whether heparin was indeed removed from the PCC by this treatment.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Recent reports have described the use of these agents in patients with ICrH, 25 , 26 , 32 , 33 although the mechanistic basis for their effectiveness is controversial. 34 Furthermore, their efficacy may be restricted in the presence of higher anti-FXa levels, 35 and the reports provide limited or no information regarding baseline anti-FXa activity. Relative to previously available therapies, andexanet represents a therapeutic advance given its specific, rapid, and biologically relevant mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…This may be an important consideration given the results of an in vitro investigation noting insufficient tissue factor initiated thrombin generation with 4F-PCC at apixaban and rivaroxaban concentrations above 75 ng/mL. 51 Similarly, in healthy volunteers with an average rivaroxaban trough concentration of 130 ng/mL, punch biopsy bleeding was not reduced following 4F-PCC (50 units/kg) although endogenous thrombin potential did increase compared to saline controls. 52 Nevertheless, our cohort represents our observations in a real-world setting of FXa-inhibitor-related bleeding.…”
Section: Discussionmentioning
confidence: 99%